2013 47th International Carnahan Conference on Security Technology (ICCST) 2013
DOI: 10.1109/ccst.2013.6922078
|View full text |Cite
|
Sign up to set email alerts
|

Automatic region segmentation for high-resolution palmprint recognition: Towards forensic scenarios

Abstract: Esta es la versión de autor del congreso publicado en: This is an author produced version of a paper published in: Abstract-Recently, a novel matching strategy based on regional fusion for high resolution palmprint recognition arises for both forensic and civil applications, under the concept of different regional discriminability of three palm regions, i.e., interdigital, hypothenar and thenar. This matching strategy requires accurate automatic region segmentation techniques since manual region segmentation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, this evaluation suffers from some limits, in particular when tests strike structured on conditions, different criteria and/or for the several database, making immediate comparisons harder. We will compare our work with an original work which was introduced by (Wang et al, 2013a) as shown in Table 3. Where (Wang et al, 2013a) proposed an algorithm to segment the palmprint image called automatic segmentation into three regions and used the last 50 subjects (50×2×8) from the THUPALMLAB database to evaluate their work.…”
Section: Experiments Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this evaluation suffers from some limits, in particular when tests strike structured on conditions, different criteria and/or for the several database, making immediate comparisons harder. We will compare our work with an original work which was introduced by (Wang et al, 2013a) as shown in Table 3. Where (Wang et al, 2013a) proposed an algorithm to segment the palmprint image called automatic segmentation into three regions and used the last 50 subjects (50×2×8) from the THUPALMLAB database to evaluate their work.…”
Section: Experiments Resultsmentioning
confidence: 99%
“…We will compare our work with an original work which was introduced by (Wang et al, 2013a) as shown in Table 3. Where (Wang et al, 2013a) proposed an algorithm to segment the palmprint image called automatic segmentation into three regions and used the last 50 subjects (50×2×8) from the THUPALMLAB database to evaluate their work. They used the segmentation error parameter to measure the accuracy of the segmentation algorithm which is indicated in (Goumeidane and Khamadja, 2010).…”
Section: Experiments Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Wang et al [31] further developed an automatic region segmentation method, which could segment an image into three regions, namely, interdigital, thenar, and hypothenar regions, by applying a Canny edge detector to a full palmprint image, detecting the first data point by the convex hull, and estimating based on the position and direction of the first data point. Finally, the regions were segmented based on these points.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The subset of THUPALMLAB includes the palmprint images from the last 50 subjects with 100 palms, that is, 800 ( = 50 × 2 × 8) images. Moreover, automatic segmentation based on datum points using the method proposed in [16] is also performed on the same subset. As reported in [16], there are 702 images segmented successfully in the subset of THUPALMLAB, among which there are 85 palms obtaining successful segmentation for their complete eight-image sets.…”
Section: Regional Discriminabilitymentioning
confidence: 99%